Language access differentially alters functional connectivity during emotion perception across cultures - Leshin, Joseph; Carter, Maleah J.; Doyle, Cameron M.; Lindquist, Kristen A. (Frontiers in Psychology, 2024)
It is often assumed that the ability to recognize the emotions of others is reflexive and automatic, driven only by observable facial muscle configurations. However, research suggests that accumulated emotion concept knowledge shapes the way people perceive the emotional meaning of others' facial muscle movements. Cultural upbringing can shape an individual's concept knowledge, such as expectations about which facial muscle configurations convey anger, disgust, or sadness. Additionally, growing evidence suggests that access to emotion category words, such as "anger," facilitates access to such emotion concept knowledge and in turn facilitates emotion perception. To investigate the impact of cultural influence and emotion concept accessibility on emotion perception, participants from two cultural groups (Chinese and White Americans) completed a functional magnetic resonance imaging scanning session to assess functional connectivity amongst brain regions during emotion perception. Across four blocks, participants were primed with either English emotion category words ("anger," "disgust") or control text (XXXXXX) before viewing images of White American actors posing facial muscle configurations that are stereotypical of anger and disgust in the United States. We found that when primed with "disgust" versus control text prior to seeing disgusted facial expressions, Chinese participants showed a significant decrease in functional connectivity between a region associated with semantic retrieval (the inferior frontal gyrus) and regions association with semantic processing, visual perception, and social cognition. Priming the word "anger" did not impact functional connectivity for Chinese participants relative to control, and priming neither "disgust" nor "anger" impacted functional connectivity for White American participants. These findings provide preliminary evidence that emotion concept accessibility differentially impacts perception based on participants' cultural background.